2003
DOI: 10.2176/nmc.43.181
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Pituitary Adenomas From Other Sellar and Parasellar Tumors by 99mTc(V)-DMSA Scintigraphy

Abstract: Pentavalent technetium-99m dimercaptosuccinic acid [ 99m Tc(V)-DMSA] scintigraphy was evaluated for the differentiation of pituitary adenomas, especially non-functioning adenomas, from other sellar and parasellar lesions. Diffuse 99m Tc(V)-DMSA accumulation within the tumor was found in seven of seven non-functioning, three of four growth hormone-secreting, and seven of eight prolactin-secreting adenomas, but only partial accumulation in only two of 16 non-pituitary adenomas and normal pituitary glands. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
2
4
0
1
Order By: Relevance
“…Consistent with these findings are the results of a few studies indicating that the 99m Tc(V)-DMSA scintigraphy showed an overall sensitivity ranging from 71 to 95% in detecting PAs 4345. Furthermore, 99m Tc-MIBI was found to have a strong affinity for PA, but not the normal pituitary gland 36,37.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Consistent with these findings are the results of a few studies indicating that the 99m Tc(V)-DMSA scintigraphy showed an overall sensitivity ranging from 71 to 95% in detecting PAs 4345. Furthermore, 99m Tc-MIBI was found to have a strong affinity for PA, but not the normal pituitary gland 36,37.…”
Section: Discussionsupporting
confidence: 78%
“…Kunishio et al 38 suggest that 99m Tc-MIBI SPECT may be a useful technique for the diagnosis of PA, with an overall sensitivity of 85%. Accumulation of these tracers is generally related to the affinity for the tissue or lesions, not the size of the lesion 36,37,4345, which was also the case in our study.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The delayed uptake ratio, retention ratio, and retention index are higher for the malignant tumors as compared to the benign pathology. Tc-99m (V) DMSA also demonstrated superiority over Tl-201 imaging for primary and metastatic brain tumors[ 55 56 57 58 59 60 ] [ Table 2 ].…”
Section: Pentavalent Dimercaptosuccinic Acid (Tc-99m (V) Dmsa)mentioning
confidence: 99%